EFFECT OF STUDENT’S TEAM ACHIEVEMENT DIVISION ON STUDENT’S ACADEMIC ACHIEVEMENT IN CHEMISTRY (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
Due to the increasing diverse nature of the world’s education system, it is important that learning strategies are beneficial in educating a wide variety of students. For the retention and comprehension of the subject matter taught in the classrooms, teachers must engage students and provide them with the proper social skills needed to succeed beyond the classroom environment. The focus of the present study investigated the effect of a form of cooperative learning instruction that is students’ team achievement division (STAD) with that of traditional lectures method. The population of the study was all the students studying chemistry at higher secondary level in Rivers state, Nigeria. 30 students of chemistry grade  12 in government higher  secondary school Jamrud were selected as a convenient sample of the study. The students were divided into two groups one was called control group and the other was experimental group based on stratified random sampling techniques. The true experimental design of the posttest only control group design was applied in this study. The control group was taught with the traditional lecture method while the  experimental  group with the  cooperative learning instruction STAD. Students academic achievements were find out by teacher made test composed of multiple choice questions, short questions and long questions. The credit of the test was of 50 marks, the posttest consist of multiple choice questions of 16 marks, short questions of 24 marks and one long question of two subsections having 10 marks. Student ttest of non-dependent sample was used to analyze the data. The result showed that the students’ achievements of both the groups were not significant. The implications were discussed.